THE INFLUENCE OF CAPITAL STRUCTURE, WORKING CAPITAL ROUND, AND INTELLECTUAL CAPITAL STRUCTURE ON CORPORATE VALUE IN FOOD AND BEVERAGES SECTOR MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE IN 2015-2018 - Susanto Wibowo; Ronaldo J. (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
This study aims to examine the effect of capital structure, working capital turnover, and intellectual capital structure on firm value. The sampling method uses purposive sampling. Companies with criteria in the food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange during 2015-2018. The population is 51 companies and sampling is 14 companies. Data analysis techniques using statistical tests: multiple linear regression, descriptive testing, data normality test, heteroskedasticity test, multicollinearity test, determination test, t-test, and F test. The results showed that the company's capital structure and working capital turnover significantly had a positive effect on firm value. While the intellectual capital structure does not affect the value of the company.